2021
DOI: 10.1097/mbc.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic hemostasis assays in septic, critically ill coronavirus disease 2019 patients: a practical guide for clinicians

Abstract: It is well known that coronavirus disease (COVID-19) is associated with a coagulopathy characterized by a prothrombotic state of DIC different from the usual sepsis induced DIC with significant vascular thrombosis and worsening outcomes. This hypercoagulability results in enhanced thrombin generation and fibrin formation. Routine coagulation tests, such as the prothrombin time and the activated partial thromboplastin time, do not always actively reflect this state. Thrombelastography (TEG), appears therefore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The COVID-19 pandemic has elevated the need for rapid POC testing to gauge the COVID-19 patient's hemostatic competence, thus ushering in accelerated utilization of the VHAs to diagnose and treat patients with CAC [23,134,135,150,151,153,165,166]. The hypercoagulopathy of CAC inversely mirrors the hypocoagulopathy of many other areas of clinical medicine where hypocoagulopathies can quickly evolve in the medical and surgical intensive care units, obstetrical units, and operating theaters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has elevated the need for rapid POC testing to gauge the COVID-19 patient's hemostatic competence, thus ushering in accelerated utilization of the VHAs to diagnose and treat patients with CAC [23,134,135,150,151,153,165,166]. The hypercoagulopathy of CAC inversely mirrors the hypocoagulopathy of many other areas of clinical medicine where hypocoagulopathies can quickly evolve in the medical and surgical intensive care units, obstetrical units, and operating theaters.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of heparinase to one of the cups allows the VHA assays to quantify the heparin affect, and these assays are therefore used frequently in liver transplantation and cardiac surgery. Most recently, they have been used to monitor ECMO patients, as well as heparinized COVID-19 patients [36,114,[133][134][135][136]. The assessment of non-thrombin-based platelet activation/inhibition can be assayed using TEG/PM ® and Multiplate ® , which is often used in concert with ROTEM ® .…”
Section: Vhas Reflecting Anticoagulationmentioning
confidence: 99%
“…3,4 VET analysis has also been proposed as a powerful tool for the study of the global hemostatic status of COVID-19 patients. 25 Especially, these studies have focused on the analysis of patients with poor prognosis such as those admitted to the ICU or with ARDS, revealing that VET analysis could be established as a promising tool to predict thrombotic complications and thus optimize the diagnosis and treatment of COVID-19 patients. 26 Our results showed that a high percentage of patients had altered parameters of clot stiffness, mainly due to the contribution of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…VET analysis has also been proposed as a powerful tool for the study of the global hemostatic status of COVID-19 patients [24]. Especially, these studies have focused on the analysis of patients with poor prognosis such as those admitted to the ICU or with ARDS, revealing that VET analysis could be established as a promising tool to predict thrombotic complications and thus optimize the diagnosis and treatment of COVID-19 patients [25].…”
Section: Discussionmentioning
confidence: 99%